PARALLEL PROCESSING SYSTEM - YOSHIZAWA TOSHIMASA (2024)
To provide a parallel processing system and a method for increasing calculation speed in architectural structure analysis through parallel processing by a plurality of information processors.SOLUTION: A parallel processing system includes: means for storing, with respect to a modeled object of an architectural structure subject to structural analysis, information on a relational expression of load vector=overall stiffness matri (band matrix)×displacement vector; means for setting, with a diagonal term as a band matrix, an upper left square matrix and a lower right square matrix so that a square-shaped overlapping part whose side size is the same as a band width of the band matrix is formed; means for calculating a value of a corresponding displacement vector by solving the above relational expression corresponding to the upper left square matrix in one information processor; means for calculating, in another information processor, the value of the corresponding displacement vector by solving the above relational expression corresponding to the lower right square matrix; and means for recalculating, on the basis of the above calculation result, a value of the displacement vector corresponding to the overlapped part.SELECTED DRAWING: Figure 2 【課題】複数の情報処理装置による並列処理によって建築物の構造解析における計算速度の高速化を図る並列処理システム及び方法を提供する。【解決手段】並列処理システムは、構造解析の対象となる建築物をモデル化したものに関し、荷重ベクトル＝全体剛性行列（帯行列）×変位ベクトルとする関係式に関する情報を記憶する記憶手段と、帯行列の対角項を対角線とし、一辺の大きさが帯行列のバンド幅と同じである正方形形状の重複部が形成されるように、左上側正方行列と右下側正方行列とを設定する手段と、一の情報処理装置において、左上側正方行列に対応する上記関係式を解くことによって、対応する変位ベクトルの値を算出する手段と、他の情報処理装置において、右下側正方行列に対応する上記関係式を解くことによって、対応する変位ベクトルの値を算出する手段と、上記の算出結果に基づいて、重複部に対応する変位ベクトルの値を再計算する手段と、を有する。【選択図】図２